Determination of the effect of functional single-nucleotide polymorphisms associated with glycerolipid synthesis on intramuscular fat deposition in Korean cattle steer - Kim, Hyeongrok; Oh, Dong-Yep; Lee, Yoonseok (Archiv für Tierzucht, 2021)
Intramuscular fat deposition in the longissimus dorsi muscle (LM) of Korean cattle steer is regulated by several genes related to lipid metabolism. One of these genes encodes the enzyme bovine glycerol-3-phosphate acyltransferase, mitochondrial (GPAM), which is located on the mitochondrial outer membrane and catalyzes the initial and committed step of glycerolipid synthesis in lipid metabolism of cattle. Previous studies have shown that the 3′-untranslated region (UTR) of the GPAM is quite extended and contains a polyadenylation signal site, erythroid 15-lipoxygenase differentiation control elements (15-LOX-DICEs), and cytoplasmic polyadenylation elements (CPEs) that affect the regulation of triacylglycerol synthesis. Therefore, the aim of this study was to identify single-nucleotide polymorphisms (SNPs) related to the regulation of glycerolipid synthesis in the 3′-UTR of GPAM and to verify the function of SNPs affecting the deposition of intramuscular fat in Korean cattle steer. In the present study, 11 SNPs were discovered in the 3′-UTR of GPAM. Among these SNPs, g.54853A>G, g.55441A>G, and g.55930C>T were significantly associated with marbling score in a Korean cattle steer population and were strongly correlated with each other within the GPAM gene. Furthermore, based on the results predicted by the RNAhybrid program, four putative microRNAs (miRNAs) were identified, and the above SNPs were found to present in the seed region of these miRNAs. These miRNAs have a differential binding affinity for each allele of SNPs g.54853A>G, g.55441A>G, and g.55930C>T. The in vivo evidence of intramuscular fat deposition in the LM tissue showed that these SNPs affected the regulation of intramuscular fat deposition in Korean cattle steer. Thus, the g.54853A>G, g.55441A>G, and g.55930C>T could be considered as causal mutations regulating intramuscular fat deposition in Korean cattle steer.